STRATEGI PENGEMBANGAN PARIWISATA PANTAI GANDORIAH KOTA PARIAMAN PROVINSI SUMATERA BARAT - Ananda Setia Ningsih; Hartuti Purnaweni; Budi Puspo Priyadi (Journal of Public Policy and Management Review, 2022)
In formulating tourism development strategies, there are analytical tools used in formulating tourism development strategies. The analytical tool used here is a SWOT analysis. This study aims to describe and analyze the potential of tourist attractions and the condition of the tourist attraction of Gandoriah Beach and formulate a suitable development strategy for Gandoriah Beach tourism. This study uses a descriptive type with a mixed method approach (combination). The results of this study indicate that Gandoriah Beach tourism has a potential attraction in the form of natural tourism, namely marine tourism with sloping and wide beaches with views of offshore islands. The condition of the potential tourist attraction owned by Gandoriah Beach is quite good and the tourism development strategy of Gandoriah Beach, among others: (1) intensify tourism promotion using social media and print media by displaying the advantages of tourist destinations and festivals typical of Gandoriah Beach; (2) complete tourism supporting facilities and infrastructure; (3) improve the development of small islands on Gandoriah Beach, especially Angso Duo Island to increase tourist interest in traveling to Gandoriah Beach; (4) maintain the consistency of tourist entrance fees which are currently relatively cheap in order to increase the number of visitors.